Economic Growth, Inflation and Growth of Islamic Bank in Indonesia during Covid-19 - Lina Marlina; Sudana Sudana (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of economic growth and inflation on the growth of Islamic banks during the Covid-19 period. The data used is time series data or time series from January 2019 to June 2021. The method used in this study is the method of causality (cause and effect) with the Ordinary Least Squared (OLS) approach, namely the linear least squares method to estimate the unknown parameters in the linear regression model. From the results of the regression test, there is no significant effect between economic growth and inflation on the growth of Islamic banks in the period January 2019 to June 2021.